Deposition of cubic tungsten carbide coating on metal substrates at sputtering of electric discharge plasma; Journal of Physics: Conference Series; Vol. 1393 : Gas Discharge Plasmas and Their Applications (GDP 2019) - Sivkov A. A. Aleksandr Anatolyevich; Shanenkov I. I. Ivan Igorevich; Ivashutenko A. S. Alexander Sergeevich; Nikitin D. S. Dmitry Sergeevich; Shanenkova Yu. L. Yuliya Leonidovna; Rakhmatullin I. A. Ilyas Aminovich (2019, 2019)
Title screen